PENGARUH MODEL PEMBELAJARAN PROBLEM POSING TERHADAP MOTIVASI BELAJAR DI SMP NEGERI 1 MAKASSAR - Salama, Muhammad Arisullah; Syahid, Akhmad; Surani; Bunyamin, Andi; Syahrul, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the Problem Posing learning model on the learning motivation—both intrinsic and extrinsic—of eighth-grade students in the Islamic Religious Education subject at SMP Negeri 1 Makassar. The study employs a quantitative approach using an *ex post facto* method. The population consists of all 327 eighth-grade students at SMP Negeri 1 Makassar. A sample of 62 students was selected using Slovin's formula with a 10% margin of error. Data collection involved questionnaires and documentation, while the research instrument utilized a Likert scale. Data analysis was conducted using SPSS software, encompassing descriptive analysis, validity and reliability testing, assumption testing, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination. The results indicate that the Problem Posing learning model has a positive and significant effect on students' intrinsic learning motivation. This is evidenced by a calculated t-value of 6.000 (exceeding the t-table value of 2.001) and a significance value of 0.001 (below 0.05). The Problem Posing model also has a positive and significant effect on extrinsic learning motivation, with a calculated t-value of 4.701 (exceeding the t-table value of 2.001) and a significance value of 0.001 (below 0.05). The R-Square values ​​indicate that the Problem Posing model contributes 67.5% to intrinsic motivation and 50.9% to extrinsic motivation. Thus, the Problem Posing learning model serves as an effective alternative for enhancing student learning motivation in Islamic Religious Education.